2012
DOI: 10.1542/peds.2012-2758
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure in Children

Abstract: Pesticides are a collective term for a wide array of chemicals intended to kill unwanted insects, plants, molds, and rodents. Food, water, and treatment in the home, yard, and school are all potential sources of children’s exposure. Exposures to pesticides may be overt or subacute, and effects range from acute to chronic toxicity. In 2008, pesticides were the ninth most common substance reported to poison control centers, and approximately 45% of all reports of pesticide poisoning were for children. Organophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
113
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(125 citation statements)
references
References 181 publications
2
113
0
10
Order By: Relevance
“…They are atached to the nicotinic receptors of the postsynaptic membranes from both nerve and muscle cells and thus disrupt the transmission of the nervous inlux into the central and peripheral nervous system. Additionally, this interaction with the nicotinic receptors determines their desensitization, leading to a loss of synaptic transmission of the nervous impulse [6,7]. In recent years, some studies have suggested that neonicotinoids have a negative impact on bees near crops exposed to neonicotinoids.…”
mentioning
confidence: 99%
“…They are atached to the nicotinic receptors of the postsynaptic membranes from both nerve and muscle cells and thus disrupt the transmission of the nervous inlux into the central and peripheral nervous system. Additionally, this interaction with the nicotinic receptors determines their desensitization, leading to a loss of synaptic transmission of the nervous impulse [6,7]. In recent years, some studies have suggested that neonicotinoids have a negative impact on bees near crops exposed to neonicotinoids.…”
mentioning
confidence: 99%
“…The use of synthetic pesticides leads to many ecological problems. The most important negative impacts include ecological imbalance, high toxicity, residues in soil and water that affect human and animal health (Casida 2012;Roberts & Karr 2012), and the resistance of Culex against insecticides (Gordon & Ottea 2012). It was found that Culex populations could develop resistance on account of the widespread use of insecticides (Jones et al 2012).…”
mentioning
confidence: 99%
“…Varios estudios a lo largo de la historia han intentado asociar la presencia de malformaciones congénitas con factores de riesgo, algunos mencionan como factores de riesgo evidenciados: edad materna (5,6) avanzada, bajo peso y talla para la edad gestacional . Otros mencionan al retraso del crecimiento fetal, antecedentes de malformaciones congénitas en la familia, factores físicos y enfermedades agudas de la (6) madre en el primer trimestre del embarazo .…”
Section: Introductionunclassified